Impacts of social isolation stress in safety learning and the structure of defensive behavior during a spatial-based learning task involving thermal threat - Villalon, Stephanie A.; Felix-Ortiz, Ada C.; Lozano-Ortiz, Kelly; McCarrey, John R.; Burgos-Robles, Anthony (Frontiers in Behavioral Neuroscience, 2024)
Safety learning during threat and adversity is critical for behavioral adaptation, resiliency, and survival. Using a novel mouse paradigm involving thermal threat, we recently demonstrated that safety learning is highly susceptible to social isolation stress. Yet, our previous study primarily considered male mice and did not thoroughly scrutinize the relative impacts of stress on potentially distinct defensive mechanisms implemented by males and females during the thermal safety task. The present study assessed these issues while considering a variety of defensive behaviors related to safety-seeking, escape, coping, protection, ambivalence, and risk-taking. After a two-week social isolation stress period, mice were required to explore a box arena that had thermal threat and safety zones (5 vs. 30°C, respectively). Since visuospatial cues clearly differentiated the threat and safety zones, the majority of the no-stress controls (69–75%) in both sexes exhibited optimal memory formation for the safety zone. In contrast, the majority of the stress-exposed mice in both sexes (69–75%) exhibited robust impairment in memory formation for the safety zone. Furthermore, while the control groups exhibited many robust correlations among various defensive behaviors, the stress-exposed mice in both sexes exhibited disorganized behaviors. Thus, stress severely impaired the proper establishment of safety memory and the structure of defensive behavior, effects that primarily occurred in a sex-independent manner.